Analisis Persebaran Ruang Terbuka Hijau (RTH) Di Pusat Kota Tasikmalaya Menggunakan Sistem Informasi Geografis (SIG) Studi Kasus : Kecamatan Cihideung Dan Kecamatan Tawang - Rendi Mulyana; Pajar Sutrisna; Pasha Paisal Rahman; Siti Padjarajani; Cahya Darmawan (Geosfera: Jurnal Penelitian Geografi, 2025)
The rapid growth of commercial and residential activities in city centers often exerts pressure on the existence of green spaces. This study analyzes the condition, adequacy, and spatial distribution of Green Open Space (GOS) in the central area of Tasikmalaya City, specifically in Cihideung and Tawang Districts, utilizing Geographic Information Systems (GIS). The research employs a descriptive qualitative approach supported by field surveys and spatial data analysis to map locations and calculate GOS areas. The results indicate a significant deficit in GOS availability in both districts, with an estimated area of only 15-20%, falling well below the minimum standard of 30% mandated by Law Number 26 of 2007. In terms of distribution, GOS is uneven and fragmented; green spaces are concentrated primarily in public facilities and city parks such as Dadaha Park and the City Square, while high-density residential areas and commercial zones lack sufficient vegetation. The study concludes that spatial planning interventions are required through the optimization of residual spaces, revitalization of existing GOS, and implementation of green architecture (such as vertical gardens) to address ecological imbalances caused by urbanization pressures in the city center.